INTERNALIZATION MODEL OF SOFT SKILL OF STATE DEFENSE FOR STUDENTS OF FACULTY OF SOCIAL AND POLITICAL SCIENCES THROUGH INTEGRATIVE AND SUSTAINABLE ACTIVITIES - Machya Astuti Dewi; Asep Saepudin; Muharjono Muharjono; Indro Herry Mulyanto; Kurnia Arofah (Indonesia Defense University, 2019)
This article is the result of institutional research, which aims to develop a model of internalization of state defense soft skills for FISIP students of UPN